PENGARUH LITERASI KEUANGAN, LITERASI DIGITAL DAN INTENSITAS MENONTON KONTEN TERHADAP PERILAKU KONSUMTIF PENGGUNA TIKTOK PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - Wahyuni, Laili; Sobakh, Nurus; Nurhayati, Dies (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
Rapid advances in information and communication technology have given rise to various social media platforms, one of which is TikTok, which presents information in various formats. As a result, consumer behavior is increasingly widespread due to the ease of purchasing goods. People are now trying to meet their needs while pursuing goods that are not only necessary but also desired. This research aims to examine separately and simultaneously the influence of Financial Literacy, Digital Literacy, and Content Watching Intensity on the consumer behavior of TikTok users. The method used in this research is quantitative with a deductive approach. The research population consisted of 333 students, with a sample of 77 respondents determined using the Slovin formula. Data was collected through questionnaires and tested using validity and reliability tests. Data analysis was carried out using multiple linear regression, classical assumption test, t test, F test, and coefficient of determination (R²). The results of the research show that there is a partial influence of financial literacy on consumptive behavior with a significant value of 0.000 < 0.05, there is a partial influence of digital literacy on the consumptive behavior of TikTok users with a significant value of 0.002 < 0.05, there is no partial influence of the intensity of watching content. on the consumptive behavior of TikTok users with a significant value of 0.835 > 0.05 and there is an influence of financial literacy, digital literacy and the intensity of watching content simultaneously on the consumptive behavior of TikTok users with an F-count value of 5.888 > F-table 2.73 and a significant value of 0.001 < 0.05.